2003
DOI: 10.1002/pds.770
|View full text |Cite
|
Sign up to set email alerts
|

A study of drug use during pregnancy in a teaching hospital in western Nepal

Abstract: Information on the use of drugs during pregnancy is scarce and rather anecdotal. Careful consideration of the benefit to the mother and the risk to the fetus is required when prescribing drugs during pregnancy. The aim of this study was to gain knowledge on this issue in western Nepal. 2156 prescriptions of pregnant women were collected at random from the antenatal care (ANC) in obstetrics out-patient department (OPD) at Manipal Teaching Hospital (MTH), Nepal and analyzed for this study. The mean maternal age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
30
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 17 publications
9
30
0
Order By: Relevance
“…19 In moderate anemia, iron salts were given in most of patients as to overcome the need of increased iron requirement during pregnancy. Ferrous fumarate and Ferrous ascorbate was prescribed in 144 (57.6%) and 45 (18%) patients which is similar to other studies in United States (72%) 19 , Switzerland (65%) 20 , West Nepal (72.8%) 21 and Egypt (86%) 22 But less than one study. 23 Injectable iron like iron sucrose was prescribed to moderate and severe anemia when oral iron was not tolerated and gives faster response.…”
Section: Discussionsupporting
confidence: 67%
“…19 In moderate anemia, iron salts were given in most of patients as to overcome the need of increased iron requirement during pregnancy. Ferrous fumarate and Ferrous ascorbate was prescribed in 144 (57.6%) and 45 (18%) patients which is similar to other studies in United States (72%) 19 , Switzerland (65%) 20 , West Nepal (72.8%) 21 and Egypt (86%) 22 But less than one study. 23 Injectable iron like iron sucrose was prescribed to moderate and severe anemia when oral iron was not tolerated and gives faster response.…”
Section: Discussionsupporting
confidence: 67%
“…Oral iron intake is the treatment of choice, and almost all women can be treated effectively with oral preparations 21 . All pregnant women attending antenatal OPD were prescribed iron and folic acid as a positive result compared to other studies where the percentages of women prescribed iron & folic acid were -West Africa (33.33%) 22 , Germany (iron-54%) 23 , Nepal (72.8%) 24 and Pakistan study (79.4%) 25 . Thus Findings of this study showed that all eligible pregnant women were provided with prophylactic iron and folic acid therapy.…”
Section: Main Findings Of the Studymentioning
confidence: 87%
“…Rohra DK et al [11] found majority of drugs prescribed during the 3 rd trimester of pregnancy (55.4%) and average number of drugs prescribed was 1.66+ 0.14. In the study of Das B et al [12] most of the female received multiple drugs which included mostly nutritional supplements like iron, vitamins. Polypharmacy was also reported by Kumari R et al [13] in their study which was conducted in Lucknow, north India and they found lowest average of number of drugs per prescription was 2.6 + 1.6 at tertiary level.…”
Section: Discussionmentioning
confidence: 99%